Congenital vitiligo with positive paternal history − a rare case report - Niharika Jha; Vanya Narayan (Wolters Kluwer Medknow Publications, 2020)
Vitiligo is considered to be an acquired skin disorder in which melanocytopenia occurs. It is characterized by development of achromic patches on skin. Most of the patients develop this disease in the second or third decade of life. We present a case of a 7 month old child who had depigmented patches on skin since birth, which questions the concept of acquired etiology of vitiligo.